Fatigue Modeling and Mechanical Performance of Additively Manufactured and Commercial Polylactic Acid to Support Sustainable Development Goals (SDGs) Completed with Bibliometric Analysis - Ziadoon M. R. Al-hadrayi; Samar M. Challabi; Mujtaba A. Flayyih; Emad Kadum Njim (ASEAN Journal for Science and Engineering in Materials, 2027)
This study evaluates the fatigue behavior and mechanical performance of polylactic acid (PLA) produced by fused deposition modeling (FDM) and compares it with commercially manufactured PLA to support Sustainable Development Goals (SDGs) related to sustainable manufacturing. Tensile, impact, and fatigue tests were conducted to evaluate the strength, toughness, and fatigue life under cyclic loading. A fatigue crack growth model based on linear elastic fracture mechanics and Paris’ law was developed and solved numerically using MATLAB. In addition, a bibliometric analysis was conducted to identify recent research trends connecting additive manufacturing, fatigue performance, and sustainability. The results show that process-induced anisotropy and defects significantly reduce the fatigue resistance of FDM-printed PLA, while optimized infill density and raster orientation improve performance. The findings provide practical guidance for the reliable and sustainable application of additively manufactured polymer components.